Appréhender l'innovation par l'usage des TIC dans l'enseignement supérieur : questions conceptuelles et méthodologiques - Brigitte Simonnot (Centre National d'Enseignement à Distance, 2013)
Many researches deal with innovation in higher education. Except those endorsing more or less commonplace discourse, a number of these are empirical studies. The purpose of this article is not to establish a classification of those researches but to question conceptual and methodological frameworks in scientific studies related to information and communication technologies (ICT) use. Information and communication scientists tend to prefer the notion of practices to that of use(s). We start with the four approaches which marked the "practice turn" and gathered by Christian Licoppe (2008) in his "square of activity", ie distributed cognition, the psychological theory of activity developed by Engeström, ethnographic approaches / situated action and the actor-network theory. These four approaches originate from distinct disciplines and have in common the use of ethnographic methods, but with different positioning for the researcher. They also give a different place and role to objects or artifacts mobilized in activities. Digital technologies lead to further mediatisation of both content and exchanges in training and they are fully engaged in mediations. However, we question the relevance of putting technologies at the heart of issues without further developing the way actors conceive the very concepts of information and communication.